An oral first‐in‐class small molecule RSK inhibitor suppresses AR variants and tumor growth in prostate cancer. Issue 5 (1st April 2022) - Ushijima, Miho; Shiota, Masaki; Matsumoto, Takashi; Kashiwagi, Eiji; Inokuchi, Junichi; Eto, Masatoshi
Abstract: Ribosomal S6 kinase has been shown to play a key role in cellular resistance to endocrine therapy in prostate cancer through its regulation of YB‐1/androgen receptor (AR) signaling. PMD‐026, an oral first‐in‐class small molecule kinase inhibitor, is the first identified ribosomal S6 kinase inhibitor. This study investigated the effect of PMD‐026 on YB‐1/AR signaling and its antitumor effect in prostate cancer in vitro and in vivo. Castration‐resistant prostate cancer 22Rv1 cells that express high‐level AR variants were used in this study. The effect of PMD‐026 on YB‐1/AR signaling was investigated by quantitative real‐time PCR and western blot analysis. The effects of PMD‐026 on prostate cancer cells were investigated by cytotoxicity analysis, apoptosis assay, and cell cycle assay in vitro and a mouse castration model in vivo. PMD‐026 decreased YB‐1 phosphorylation as well as AR V7 mRNA and AR variant expressions in 22Rv1 cells. PMD‐026 suppressed cell proliferation alone and in combination with the second‐generation antiandrogens enzalutamide and darolutamide by inducing cellular apoptosis and G2/M arrest. In a mouse xenograft model, PMD‐026 suppressed tumor growth, and the combination of PMD‐026 and enzalutamide inhibited tumor growth more prominently than single treatments. Our results demonstrate an excellent antitumor effect of the novel ribosomal S6 kinase inhibitor PMD‐026 and the combination effect with the antiandrogen enzalutamide in castration‐resistant prostate cancer. These findings warrant a clinical trial of PMD‐026 in prostate cancer patients. Abstract : This study demonstrated an excellent antitumor effect of the novel ribosomal S6 kinase inhibitor PMD‐026 and the combination effect with the antiandrogen enzalutamide in castration‐resistant prostate cancer. These findings warrant a clinical trial of PMD‐026 in prostate cancer patients.